Deep water cuspate stromatolites of the Cryogenian Trezona Formation. Issue 2 (16th December 2021) - O'Connell, Brennan; Wallace, Malcolm W.; Hood, Ashleigh v.S.; Rebbechi, Luke; Brooks, Hannah L.
Abstract: Stromatolites and microbialites contain a rich repository of environmental and biological information. Despite extensive research, questions remain regarding the biological, chemical, and physical processes that control stromatolite macro, meso, and microstructure. We report unusual deep water cuspate stromatolites from the Cryogenian Trezona Formation, South Australia, from a mixed siliciclastic–carbonate open marine ramp setting. Cuspate stromatolite horizons develop near the base of decameter‐scale transgression–regression cycles and typically overlie decimeter‐scale irregular erosion surfaces. The cuspate structure within the stromatolites form near vertical, stacked cusp structures in cross section. In plan view, the cusps form cm‐scale sharp parallel ridges oriented perpendicular to the regional downslope direction and perpendicular to the elongation direction of stromatolites. Stromatolites colonized topographic highs of irregular erosion surfaces (often hardgrounds) and grew in carbonate supersaturated, iron‐rich marine waters in low turbidity sediment‐starved settings. Cuspate stromatolites are interpreted as forming in deep water environments during maximum transgression as condensed intervals. Their microbial metabolism may require low light and low oxygen. A deep water origin for the Trezona Formation cuspate stromatolites and other Precambrian cuspate stromatolites suggests a link between the cuspate morphology and physical/chemical (carbonate supersaturated, low light, and low oxygen) conditions of Precambrian deep water marine settings.